As relações interdisciplinares refletidas na Ciência da Informação - Lucineia Maria Bicalho (2009)
The study is focused on interdisciplinary of Information Science, using the scientific production of the area published in Brazilian specialized journals as a source of information. In the light of a theoretical framework on the disciplinary procedures of interaction, namely: multi-, inter-, and transdisciplinarity, it was proceeded the analysis of the articles produced in the information science with the objective to analyze how the relationship with other disciplines occur in research carried through in the area. The journals which were selected to review are indexed in the Qualis, the avaluation system of the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), responsible agency for assessing the post-graduation in Brazil. It was delimited a period of six years for the analysis for corresponding the two evaluations conducted by CAPES. In total 531 articles was analyzed in the four journal examined, of which a sample of 158 texts for presenting indicative properties of interaction with other areas for the development of the research was isolated. The analysis of the articles was based on the comment of characteristics of the studied object, in particular the number of authors, the academic formation and the field of performance of the authorship teams, the theoretician-conceptual basement, the used methodology, the scope of the search and results. The results had shown that the information science, recognized by the almost unanimity of its researchers, as an interdisciplinary science, does not reflect in itsresearch features that confirm this level of interaction with other disciplines, according to this vision research.